If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3v + 8 + -5 = 29 Reorder the terms: 8 + -5 + -3v = 29 Combine like terms: 8 + -5 = 3 3 + -3v = 29 Solving 3 + -3v = 29 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -3v = 29 + -3 Combine like terms: 3 + -3 = 0 0 + -3v = 29 + -3 -3v = 29 + -3 Combine like terms: 29 + -3 = 26 -3v = 26 Divide each side by '-3'. v = -8.666666667 Simplifying v = -8.666666667
| 5x+2=2(2x-3)+8 | | 3z+3/7=4z+5/7 | | 4k+7=-3+5k | | -1/3/-2/3 | | 9(2x-1)=3(6x+9) | | 8ab^3-44ab^2+20ab= | | 20x/2=5x | | 2(-6+2n)=2(3n-(6+5)) | | a^2*b^2+a*b+1/4=0 | | 20x/2=5 | | 145+8x=57+19x | | 0.20x+0.25(70)=24.5 | | 0.5x-0.33333333333333=0.25x-0.2 | | -15x^2-23x+28= | | -8k-4k=35 | | 100x/50x=50x/2 | | -0.33333333333333x+0.5=-0.25x-1 | | 1/4(x+6)=1/6(x+8) | | -0.33333333333333x+0.5=-0.25-1 | | 13x-68=179 | | 12/4x=16x/4 | | X^2+y^2-2ax=0 | | rad(3x+25)=x+7 | | 3x^2-5xy-2y^2= | | 5x+9+6x+3= | | 6/6x=89x/1 | | 3x+5+4x+7=19 | | 6*6x=89x*1 | | -9d+7-6d=-133 | | 2b^2+4b+2=0 | | 3x+2-x=6+5x-3 | | m-1/3=-9 |